The effects of ice application over the vastus medialis on the activity of quadriceps femoris assessed by muscle function magnetic resonance imaging - Kinugasa, R.; Yoshida, K.; Horii, A. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The purpose of this study was to investigate the effect of ice application for the muscle vastus medialis (VM) on the activation pattern of the quadriceps femoris muscle during repetitive knee extensions using muscle function magnetic resonance imaging (mfMRI) technique. Methods: Seven men underwent transverse relaxation time (T2)-weighted magnetic resonance imaging (spin echo, TR/TE=1500/25, 80 ms, 10 mm slice thickness and gap) of their right thigh at rest and immediately after isotonic knee extension exercise with 5 sets of 10 repetitions at a load equal to 70% of their 10 repetitions with and without skin cooling. Cooling over surface skin of the VM was carried out for 3 min before and during 60-s of each rest interval between the knee extension exercise. Results: The relative change in T2 of the muscle vastus intermedius increased significantly more by skin cooling than the control (p<0.01), but not the muscle rectus femoris (RF), muscle vastus lateralis, and VM. Conclusion: These results suggest that selective skin cooling combined with repeated muscle contraction facilitates the activation of other synergistic muscles, making this technique useful for activating the agonist muscles expected for injured muscle in training and rehabilitation.